Hasan al-Turabi’s approach to Qur’ānic exegesis - Ibrahim, Esam Eltigani Mohamed (Intellectual discourse, 2014)
Author of numerous books in Islamic Studies, Hasan al-Turabi is considered an eminent and influential figure in international Islamic movements as well as a controversial thinker. Among his most prominent and most recent works is his Qur’ānic exegesis entitled "al-Tafsīr al-Tawḥīdī". This study discusses al-Turabi’s fundamental postulates in his exegesis. Applying analytic and inductive methodologies, the research concludes that although al-Tafsīr al-Tawḥīdī focuses on Islamic renewal and the establishment of an Islamic State, al-Turabi took this opportunity to express his general beliefs, which subsequently served as the foundation of his exegesis. The study also reveals that al-Tafsīr al-Tawḥīdī can be classified among the modernist exegetical trends in tafsīr as it claims that the Qur’ān is open to personal interpretation and advances the argument on the historicity of both the Sunnah of the Prophet (SAW) and the tradition of tafsīr.